The influence of the stiffness of GelMA substrate on the outgrowth of PC12 cells. Issue 1 (18th January 2019) - Wu, Yibing; Xiang, Yang; Fang, Jiehua; Li, Xiaokeng; Lin, Zunwen; Dai, Guangli; Yin, Jun; Wei, Peng; Zhang, Deming
Abstract : Recent studies have shown the importance of cell–substrate interaction on neurone outgrowth, where the Young's modulus of the matrix plays a crucial role on the neurite length, migration, proliferation, and morphology of neurones. In the present study, PC12 cells were selected as the representative neurone to be cultured on hydrogel substrates with different stiffness to explore the effect of substrate stiffness on the neurone outgrowth. By adjusting the concentration of gelatin methacryloyl (GelMA), the hydrogel substrates with the variation of stiffnesses (indicated by Young's modulus) from approximately 3–180 KPa were prepared. It is found that the stiffness of GelMA substrates influences neuronal outgrowth, including cell viability, adhesion, spreading, and average neurite length. Our results show a critical range of substrate's Young's modulus that support PC12 outgrowth, and modulate the cell characteristics and morphology. The present study provides an insight into the relationship between the stiffness of GelMA hydrogel substrates and PC12 cell outgrowth, and helps the design and optimization of tissue engineering scaffolds for nerve regeneration.